Tri-layer tissue engineering heart valve based on collagen, elastin and hyaluronic acid - Ma, Z (2024)
Valvular heart disease is one of the leading causes of death globally, nonetheless, it is treatable via clinical heart valve replacement. Between the clinically used mechanical and bioprosthetic valves, thrombosis, calcification, and incompatibility to somatic growth have been the limiting factors. Tissue engineering heart valve scaffolds, especially those constructed with naturally derived materials, have proven biocompatible and promising candidates for future-generation heart valve replacements. Instead of the commonly used polymeric collagen, this thesis selected type I bovine atelocollagen, together with hyaluronic acid (HA) and a novel type of fibrillar gel elastin, as the scaffold-constructing materials, for the anti-immunogenicity of atelocollagen and the composition resemblance of the natural aortic heart valve extracellular matrix. The self-assembly of atelocollagen into fibrillar collagen was successfully proven, and highly porous (> 98 %) collagen-based single-layer scaffolds with desired interconnective microstructure were subsequently fabricated and crosslinked by lyophilisation and the EDC/NHS chemistry. The effect of collagen sources, crosslinking, and HA incorporation was studied in microstructure, chemical structure, and mechanical properties. It was shown that crosslinking improved the scaffold stiffness but compromised the extensibility. HA infiltration further stiffened the structure, whereas premixing HA with collagen yielded mechanically inferior structures in the non-hydrated state. Hydration was shown to drastically reduce scaffold stiffness in the self-deflection bending test. Two designs of tri-layer scaffolds resembling the natural heart valve structurally were subsequently fabricated, with smooth interlayer transition and no visible sign of structure delamination. The average pore size ranging from 147 to 220 μm is deemed to be suitable for cell adhesion, proliferation, and differentiation. Both designs demonstrated the desired bending anisotropy in the non-hydrated and hydrated state tested by the three-point bending test, with the bending modulus being 1208 ± 178 kPa in the with curvature (WC) direction and 1452 ± 392 kPa in the against curvature (AC) direction for non-hydrated tri-layer(ipn) scaffolds, 290 ± 48 kPa in the WC direction and 571 ± 169 kPa in the AC direction for the non-hydrated tri-layer(mix) scaffolds. Hydration reduced the bending stiffness; however, hydrated scaffolds exhibited the desired J-curve stress-strain response for biomedically oriented applications. The hydrated bending modulus tested by the self-deflection test was 5 ± 1 kPa for tri-layer(ipn) in the WC direction and 8 ± 2 kPa in the AC direction, and 4 ± 2 kPa for tri-layer(mix) WC and 6 ± 3 kPa AC. Despite the lowering effect on mechanical properties, hydration eliminated the mechanical strength difference between the two designs, rendering them both promising candidates for future in vitro and in vivo studies. In potential future applications, the interconnected and widely distributed pore size range makes the designs suitable for a variety of biomedical applications not limited to aortic heart valve replacement. Dermal tissue engineering, for example, can benefit from the designs included in this thesis for their similar composition requirements (collagen, HA, and elastin), suitable pore size range (219 ± 34 μm), and less demanding mechanical properties.